An Investigation of the Factors Influencing UAE Nationals to undertake Technical and Vocational Education - Violetta Luzie Neusuess (Technium Social Sciences Journal, 2020)
Technical and vocational skills are essential for the United Arab Emirates (UAE) to secure growth and wealth as per the UAE Vison 2021, Abu Dhabi Vision 2030 and Emiratization strategies. Gaining insights about the factors that influence Emirati students that study technical and vocational education can support the UAE to attract more Emiratis into that area. What are those major influential factors, and are there any differences related to the gender, age level, and location of living in the UAE? The factor analysis revealed five underlying factors; the career factor, the economic factor, the guidance factor, the media factor, and the social environment factor. The career factor (M = 3.48) is perceived as the most influential one, followed by the social environment factor (M = 3.32). The independent sample t-test presented a statistically significant difference between male (M = 2.8, SD = 1.066, N = 178) and female (M = 2.6, SD = 1.066, N = 250) perceptions in the economic factor (t [426] = 2.042 = 0.042, p < 0.05). The result shows that males place more emphasis on the economic aspect when considering their educational paths. The one-way ANOVA revealed a statistically significant variance in the economic factor for the location of living (F [7,420] = 4.278, p < 0.05). The research discloses that the career aspects and future job perspectives in addition to parents of national students are the most considerable influencer, which is forming the basis for this study. Differences in perceptions could be discovered for economic aspects only. The findings reveal it is essential to consider the career, economic aspect, and parents’ involvement when marketing technical and vocational education to Emirati students. Social media marketing is recommended as an advertising tool for best results.